Acute surgical site infection after total knee arthroplasty in patients with rheumatoid arthritis versus osteoarthritis - Ho-Ken Chung (Nature Portfolio, 2021)
Abstract Osteoarthritis is the main cause for total knee arthroplasty (TKA), followed by rheumatoid arthritis. Previous studies have reported conflicting results concerning the risk of surgical site infection after TKA for rheumatoid arthritis and osteoarthritis patients. Thus, this study aimed to examine whether rheumatoid arthritis patients had a higher risk of acute surgical site infection after TKA compared to osteoarthritis patients. We conducted a retrospective cohort study using Taiwan’s National Health Insurance Research Database of the whole population from 2012 to 2015, and collected the medical records of osteoarthritis patients or rheumatoid arthritis patients who underwent TKA. To evaluate the risk of acute surgical site infection in rheumatoid arthritis patients, propensity score matching was implemented for osteoarthritis patients. Acute surgical site infection was observed in 2.58% of TKA cases in rheumatoid arthritis patients and 2.66% of TKA cases in osteoarthritis patients. Rheumatoid arthritis and osteoarthritis patients had comparable risk for 90-day (odds ratio = 0.81, 95% confidence interval: 0.371–1.768) and 1-year (odds ratio = 0.463, 95% confidence interval: 0.121–1.766) surgical site infection. In conclusion, patients with rheumatoid arthritis were not at higher risk of acute surgical site infection after TKA compared to osteoarthritis patients. The current treatment strategy for patients with RA is safe and appropriate if they require TKA.